Sin³x = sin x

--> Sin x ( sin²x - 1 )

l l

l l

sin x = O sin²x - 1 = 0

l sin²x = 1

l l

.............. l

..............

Je ne sais pas quoi faire après ...

2° tg (π/3 - 2x) + tg 3x = 0

Sin (3x + π/6) - cos (x - π/3) = 0

Sin 3x = cos ( π/3 - x)

Merci d'avance.

1
c'est quoi que tu dois faire à la 1?
résoudre quoi?

Réponses

  • Utilisateur Brainly
2013-11-03T16:41:41+01:00
a) sin³x = sin x
donc sin(x)(sin(x)-1)=0
donc sin(x)=0 ou sin(x)=1
donc x=0 (2
π) ou x=π/2 (2π)

b)
tan(π/3 - 2x) + tan 3x = 0
tan(a+b)=(tan(a)+tan(b))/(1-tan(a)tan(b))
donc tan(a)+tan(b)=tan(a+b)*(1-tan(a)tan(b))
donc tan(
π/3-2x+3x)*(1-tan(π/3-2x)tan(3x))=0
donc
tan(π/3-2x+3x)=0 ou tan(π/3-2x)tan(3x)=1
donc
π/3-2x+3x=0 (π)
donc x=-
π/3 (π) ou

c) sin (3x + π/6) - cos (x - π/3) = 0
    
cos(
π/2-3x-π/6)- cos (x - π/3) = 0    
cos(π/2-3x-π/6) = cos (x - π/3)
π/2-3x-π/6=x - π/3 ou π/2-3x-π/6=-x + π/3
-4x=
- π/6 ou -2x=0
x=
π/24 (π/4) pu x=0 (π)